2015
DOI: 10.1016/j.matchar.2015.06.020
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of local deformation and stress-assisted local phase transformations in MMC foams

Abstract: Cellular structures are of growing interest for industry, and are of particular importance for lightweight applications. In this paper, a special case of metal matrix composite foams (MMCs) is investigated. The investigated foams are composed of austenitic steel exhibiting transformation induced plasticity (TRIP) and magnesia partially stabilized zirconia (Mg-PSZ). Both components exhibit martensitic phase transformation during deformation, thus generating the potential for improved mechanical properties such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Very early on, various types of foams were imaged via tomography and their behavior was studied thanks to DVC [207,11,197,181,59,15,64]. The degradation mechanisms of such materials in indentation experiments received some attention [231,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…Very early on, various types of foams were imaged via tomography and their behavior was studied thanks to DVC [207,11,197,181,59,15,64]. The degradation mechanisms of such materials in indentation experiments received some attention [231,20,22].…”
Section: Introductionmentioning
confidence: 99%
“…The MMC foam in Figure 2 serves as a very good example. Similar samples have been tested macroscopically quite extensively [2,3]. It was found that such foams behave more or less like metallic foams, and -as indicated earlier -one can identify the regimes of elasticity, plastic collapse, and densification quite well.…”
Section: A Pipeline For Materials Testingmentioning
confidence: 55%
“…For damage analysis they used very similar analysis techniques as presented in this contribution: insitu CT experiments were evaluated by using digital volume correlation (DVC) and local failure was derived from deformation field and correlated with the damaged microstructure. Berek et al [10] used in-situ compression experiments in a Xray computed tomography device to investigate the local deformation and the correlated phase transformation in the metallic phase of their MMC foam. Amsterdam et al [11] investigated the fracture behaviour of a foam, made of recycled MMC material (Al-9Si with 20 vol.-% SiC particles).…”
Section: Foamsmentioning
confidence: 99%